The growing of Social Function of Rural Society through the usage of Kenthongan - Warto Warto; Chatarina Rusmiyati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
This research is aimed to dig out the social function of Kenthongan for rural society. It uses qualitative descriptive approach for describing the meaning of kenthongan for society. The research was conducted in Sleman district, especially done in the location of Argomulyo Village, Cangkringan sub-district, Sleman District of Yogyakarta Province. Data sources are purposively decided, namely male respondents, in the age of about 60 years old, and having sufficient knowledge of kenthongan, mainly knowing the code and its hitting rhythm, the meaning of sound agreed or understood by local society,and the social function of kenthongan for the society. The data collection is conducted by direct free unstructured interview, non-participants observation, and study on documents and literatures, under qualitative data analysis. The research shows that kenthongan socially functions as a social communication tool for local society and as a society existency. In the context of its function as a social communication, kenthongan plays its role as initial warning tool of calamity, invitation to gather for discussing and working together to help each other, showing society social defense and as a reminder tool for Moslemsociety to pray on time. In the positioning context as a local society identity, kenthongan functions as conserving media and actualization of social loyalty value, as an identity of Javanese society characters and also as symbol of society life. It is recommended to the Ministry of Social to synergize with the Ministry of Communication and Information to reconsider the role and the social functioning of kenthongan for local society. Authorized local parties, such as Social Body, Culture Body, and Tourism Body need to direct all society elements to enable kenthongan becomes one of icons of YogyakartaSpecial Region